Swift Runner in Serbian Hagiographic Literature - Bojović, Dragiša P. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The paper explores the motif of swift runner from the New Testament in Serbian 13th and 14th century hagiographies. The motif, which comes from the Saint Paul’s Epistles, was used by the Serbian writers (Sava, Domentijan and Teodosije) in its sublimed variant. The term has been borrowed from The Life of Saint Sava by Domentijan as it represents poeticised theological thought of Saint Paul. The purpose of the motif is to present the Serbian heroes as winners in the race for salvation, and as such it contributes to the overall portrayal of their personalities.
Keywords: swift runner; Mount Athos; Saint Sava; Saint Simeon; Saint Paul; hagiography